The anatomical study and clinical application of the lateral ligaments of the rectum - Wu, Jing; Kuo, Zi Chong; Zhang, Changhua (Digestive Medicine Research, 2019)
The anatomical location and contents of the lateral ligaments of the rectum (LLR) should be identified in the procedure of total mesorectal excision, as well as its relationship with the middle rectal artery and pelvic plexus. However, discovering this relationship is plaguing the existence and composition of the lateral rectal ligament with confusion and misconceptions. The application of laparoscopy in rectal cancer excision is helpful in identifying the existence of the lateral ligament of the rectum. According to the anatomical study and our clinical observations, the traditional anatomical structures of the lateral ligament of the rectum do exist. It is essential for general surgeons to understand the anatomical location, contents and the technique of dissection of the lateral rectal ligament and doing so is helpful in improving the quality of life of post-operative patients.